Spiritual Care - Laumer, August (Wege zum Menschen, 2018)
The concepts of spiritual care, designed especially from a medical perspective, lead to a new appreciation of the pastoral care on patients. In view of this, the question arises as to whether Christian hospital chaplaincy is outdated and should be replaced by spiritual care. However, Christian pastoral care on patients has merits, while spiritual care is experiencing apories in the medical paradigm.